Inovasi Pembuatan Fermentasi Bawang Putih ( Black Garlic) Pencegahan Kanker Ovarium Pada Lansia Di Desa Bangun Rejo Tahun 2024 - Lisdayanti Simanjuntak; Dina Afriani; Indra Agussamad; Reja Gusmela Lumbantoruan (FKIP, Universitas Palangka Raya, 2024)
Introduction: The most common anemia in pregnancy is iron anemia, this is caused by a lack of iron intake in food due to reabsorption disorders, digestive disorders and bleeding. Method: counseling for targets is carried out orally. Results: Participants in this activity were all 46 pregnant women who visited PMB Lismayani Lubis, Simalungun Regency. Conclusion: From the results of the counseling, it was found that there were still pregnant women who did not receive enough support from their families in consuming Fe tablets, especially in reminding them of the schedule for taking Fe tablets. This community service has been carried out from August-October 2023, for exactly 3 months